2022
DOI: 10.1177/11795514221122828
|View full text |Cite
|
Sign up to set email alerts
|

Nail Folds Capillaries Abnormalities Associated With Type 2 Diabetes Mellitus Progression and Correlation With Diabetic Retinopathy

Abstract: Background: Diabetic retinopathy (DR) is an important microvascular consequence of long-term type 2 diabetes mellitus (T2DM), and it can lead to blindness if not properly diagnosed and managed. Nailfold video capillaroscopy (NVC) is a non-invasive technique for observing capillary microvasculature. Aim: We aimed to evaluate the nail folds capillaroscopic alterations in patients with T2DM by NVC and correlated the results to DR, and their relation to disease duration and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Thus, the current study, based on quantitative nailfold capillaroscopy, showed that NC parameters in diabetic patients were closely associated with the presence of DR and PDR in multivariate analyses. A previous study used another (video-based) method for nailfold capillaroscopy to quantitatively evaluate the NCs, finding that vasodilation of the NCs was a good indicator of DR; it could identify DR with an AUC of 0.75 [ 9 ]. However, this result contradicts ours.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the current study, based on quantitative nailfold capillaroscopy, showed that NC parameters in diabetic patients were closely associated with the presence of DR and PDR in multivariate analyses. A previous study used another (video-based) method for nailfold capillaroscopy to quantitatively evaluate the NCs, finding that vasodilation of the NCs was a good indicator of DR; it could identify DR with an AUC of 0.75 [ 9 ]. However, this result contradicts ours.…”
Section: Discussionmentioning
confidence: 99%
“…The current study had several limitations. First, because of the cross-sectional study design, it was not possible to discuss the time course of the association between NC alterations and DR. Second, previous reports have discussed the relationship between DR and other NC structural changes, such as avascular zones and hemorrhages [ 8 , 9 ], but we did not examine these in the current study; we focused only on quantitative NC parameters. Third, we could not obtain information on the duration of diabetes or a history of smoking, which may be possible factors involved in the progression of DR. Fourth, total cholesterol and LDL were, paradoxically, lower in diabetic patients than in the normal controls, which may be explained by the fact that 41 patients (41/83: 49.4%) were taking oral antihyperlipidemic medication.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, there is a strong interest in imaging microvascular activity in different biological tissues such as the brain [7], retina [8], oral mucosa [9], and skin [10]. Skin microvascular imaging is of particular interest since the skin is easily accessible, and monitoring changes in its microvascular activity can be used both as a tool to directly assess different skin conditions (such as psoriasis [11], burn wounds [12], systemic sclerosis [13], and skin cancer [14]), and as a means to indirectly monitor diseases that affect other organs and induce changes in skin microvasculature [2] (such as chronic kidney disease [15], diabetes [16] and peripheral vascular diseases [17]).…”
Section: Introductionmentioning
confidence: 99%